POTENCY OF SOURSOP LEAF EXTRACT AND CURCUMIN WITH MAGNETIC AND MUCUS-PENETRATING NANOPARTICLE AS COLORECTAL CANCER ALTERNATIVE THERAPY - Ebnudesita, Faiza Rahma; Dienanta, Savira Butsainah; Jannah, Ayik Rochyatul; I'tishom, Reny (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: Colorectal cancer is the second leading cause of death in the world. Currently, resection and adjuvant chemotherapy are the main therapies for colorectal cancer. Resection is an invasive procedure and chemotherapy often causes side effects due to non-specific work targets. Purpose: This study examines the potential of soursop leaf extract and curcumin with magnetic and mucus-penetrating nanoparticles as an alternative therapy for colorectal cancer. Review: Soursop leaf extract has acetogenin agent as an anti-tumor, anti-inflammatory, and cytotoxic agent that acts specifically on target organs. Curcumin from turmeric extract has antioxidant, anti-inflammatory, antimutagenic, antiangiogenic, and anticancer effects. Curcumin works molecularly on cyclooxygenase-2 (COX-2) to prevent inflammation, thereby inhibit the growth of cancer cells and reducing the risk of metastasis. Curcumin also plays a role in the inhibition of nuclear factor Îº-light-chain-enhancer of activated B (NF-ÎºB) cells, thus inhibits carcinogenesis. For drug delivery, magnetic nanoparticles and mucus-penetrating nanoparticles could be used. The magnetic field of magnetic nanoparticles generates force and torque to increase the temperature and movement of the organelles, so that apoptosis occurs from cancer cells. Mucus-penetrating nanoparticles are more resistant to mucus degradation because they can avoid mucoadhesive effects, penetrate the mucus adherent layer, and are easily absorbed by the intestinal epithelium. Conclusion: Soursop leaves, curcumin, magnetic nanoparticles, and mucus-penetrating nanoparticles are potential to be an alternative therapy for colorectal cancer.